Selected works of Mao Tse-tung - Mao, Zedong, 1893-1976 ([Foreign Languages Press], 1978)
Selected Works of Mao Tse-Tung, Volume III focuses on the views of Mao Tse-Tung on communism, revolution, fascism, national unity, and patriotism.